Effects of thermoplastic polyurethane on the properties of poly(lactic acid)/organo‐montmorillonite nanocomposites based on novel vane extruder. Issue 10 (17th October 2013) - Jia, Shikui; Qu, Jinping; Chen, Rongyuan; Wu, Chengran; Huang, Zan; Zhai, Shufeng; Liu, Weifeng; Feng, Yanhong
<x xml:space="preserve">Abstract</x> Polylactic acid (PLA)/organo‐montmorillonite (OMMT) nanocomposites toughened with thermoplastic polyurethane (TPU) were prepared by melt‐compounding on a novel vane extruder (VE), which generates global dynamic elongational flow. In this work, the mechanical properties of the PLA/TPU/OMMT nanocomposites were evaluated by tensile, flexural, and tensile tests. The wide‐angle X‐ray diffraction and transmission electron microscopy results show that PLA/TPU/OMMT nanocomposites had clear intercalation and/or exfoliation structures. Moreover, the particles morphology of nanocomposites with the addition of TPU was investigated using high‐resolution scanning electronic microscopy. The results indicate that the spherical TPU particles dispersed in the PLA matrix, and the uniformity decreased with increasing TPU content (≤30%). Interestingly, there existed abundant filaments among amount of TPU droplets in composites with 30 and 40 wt% TPU. Furthermore, the thermal properties of the nanocomposites were examined with differential scanning calorimeter and dynamic mechanical analysis. The elongation at break and impact strength of the PLA/OMMT nanocomposites were increased significantly after addition of TPU. Specially, Elongation at break increased by 30 times, and notched impact strength improved 15 times when TPU loading was 40 wt%, compared with the neat PLA. Overall, the modified PLA nanocomposites can have greater application as a biodegradable material with enhanced mechanical properties. POLYM. ENG. SCI., 54:2292–2300, 2014. © 2013 Society of Plastics Engineers